Olympiad Math | Solve Advance Algebric Expression in Simple Way

preview_player
Показать описание
Olympiad Math | Solve Advance Algebric Expression in Simple Way

Hi Friends,

Today I will teach you tips and tricks to solve the given olympiad math question in a simple and easy method.

Learn how to solve the Olympiad Question quickly with my tips and tricks.

Olympiad Exam
math olympics
olympiad exam
olympiad exam sample papers
math olympiad sample questions
math olympiada
British Math Olympiad
olympics math
olympics mathematics
olympics math activities
olympics math competition
Math Olympiad Training
mathcounts
math at work
exponential equation
system of equations
solve system of equations
solve the equation
Linear Equation
Radical Equation
Learn how to solve Olympiad Question quickly
Olympiad Mathematics
Po Shen Loh
pre
problems of class 10
problems of class 9
Standard 10 math
Standard 10 Algebra
Math for Everyone
Easy understanding Method
Math for Weak student
Quadratic Equation ssc
Quadratic Equation bank clerk mains
Quadratic Equation cgl

Thanks,
The Warrior Classes
#algebricexpression
#olympiad
#Math_problem
Рекомендации по теме
Комментарии
Автор

Nice problem and solution.

Also, after solving the quadratic, note that
(x-8) = 3 ± √10
is a unit in
ℤ[√10];
thus it's reciprocal is it's conjugate at any integer power.

Done.

pietergeerkens
Автор

solved with quadratic formula and substitution for same result, just with either positive or negative answer. nice question, and very interesting solution 👍👍

jflamingo
Автор

Logré resolverlo de una manera más sencilla, haciendo un trabajo previo completando un cuadrado de binomio (x-8)^2=6x-47 dónde me quedo que (x-8)^2 es igual 11+ raíz de 10, este valor lo reemplazo en 6x-47 lo que me da 19-6raiz de 10 de ahí racionalizo 1 partido por esa expresión, hago reducciones y llegó a 12raiz de 10

jorgepinonesjauch
Автор

P=required question
P=A-1/A
x^2-22x+111=0
x=11+sqrt 10 #1
x-8=3+sqrt 10
A=(x-8)^2
=19+6sqrt10
1/A=19-6sqrt10
P=A-1/A=12sqrt10
x=11-sqrt10 #2
The result is same as #1

에스피-ht
Автор

X^2-22X+111=0 => (X-11)^2=10, => X-8=3+-V10. => (X-8)^2=19+-6*V10 => 1: (X-8)^2=19-+6*V10. => (X-8)^2 + 1: (X-8)^2= 19+19= 38. Это моё решение.

КатяРыбакова-шд
Автор

Given equation is (x-11)+-@^2. x equals 11.

rajeevn.v.
Автор

If (x--8) =a, 1/(x--8) will be 1/a.so, the expression is ( a^2--1/a^2) I. e (a+1/a) (a--1/a). We already have( a--1/a) =6. Now(, a+1/a) =√{6^2+4=√40=+-2√10{applying conversion formula (a+b) to((a--b) and vice versa. So, the result is +-6×2√10=+-12√10.in case of integers only 12√10.

prabhudasmandal
Автор

just rewrite the quadratic as (x-8)^2 - 6(x-8) - 1 = 0 => x-8 - 1/(x-8) = 6 and proceed as above

advaithkumar
Автор

When you took square root of (a+b)^2 = 40 to give (a+b)=sqrt(40), how did you know the sign was +? From the first equation you showed that (x-8)(x-14)=1. Thus the desired quantity is (x-8)^2 - (x-14)^2 = (x-11+3)^2 - (x-11-3)^2 = 4(x-11)*3 = 12(x-11). Completing the square in the first equation gives (x-11)^2 = 10. I know the correct answer is 12sqrt(10). How to justify this choice of sign?

echandler